Defects engineering for high-performance perovskite solar cells - Feng Wang (Nature Portfolio, 2018)
Abstract Metal halide perovskites have achieved great success in photovoltaic applications during the last few years. The solar to electrical power conversion efficiency (PCE) of perovskite solar cells has been rapidly improved from 3.9% to certified 22.7% due to the extensive efforts on film deposition methods, composition and device engineering. Further investigation on eliminating the defect states in perovskite absorbers is necessary to push forward the PCE of perovskite solar cells approaching the Shockley-Queisser limit. In this review, we summarize the defect properties in perovskite films and present methodologies to control the defects density, including the growth of large size crystals, photo-curing method, grain boundary and surface passivation, and modification of the substrates. We also discuss the defects-related stability and hysteresis issues and highlight the current challenges and opportunities in defects control of perovskite films.